GAMBARAN PENGETAHUAN DAN PERILAKU 5 MOMEN CUCI TANGAN DALAM PRAKTIK KEBIDANAN PADA MAHASISWA KEBIDANAN POLTEKKES KEMENKES SEMARANG - Indira Ega Octami Nasution; Sri Setiasih; Triana Sri Hardjanti (Midwifery Care Journal, 2021)
The number of nosocomial infections continues to increase, reaching around 9% or more than 1.4 million hospitalized patients in hospitals worldwide. One of the effective prevention efforts to break the chain of infection transmission is the five moment hand hygiene. However, there is no research on the knowledge and behavior of five moment hand hygiene among midwifery students in Indonesia. The purpose of this study was to describe the knowledge and behavior of the five moment hand hygiene in midwifery practice among the students of the Poltekkes of the Ministry of Health, Semarang, class of 2017.This research is a descriptive quantitative study with a cross-sectional approach. The sampling technique used was total sampling with 47 midwifery students. Data were collected using a knowledge questionnaire that had been expertly tested by a lecturer in the Basic Skills of Midwifery, Drs, Ngadiyono, SKp., Ns., M.H.Kes. Data analysis using univariate analysis.The results showed that the level of knowledge of the midwifery students of the Poltekkes Kemenkes Semarang in the good category was 74.5% and the behavior in the good category was 100%. The conclusion of this research is that the level of student knowledge and student behavior is in good category. It is hoped that midwifery students from the Health Ministry of Health Semarang will continue to make five moments of hand hygiene a habit when practicing